Spatial–seasonal characteristics and critical impact factors of PM(2.5) concentration in the Beijing–Tianjin–Hebei urban agglomeration - Huang, Tianhang (PLoS One, 2018)
As China’s political and economic centre, the Beijing–Tianjin–Hebei (BTH) urban agglomeration experiences serious environmental challenges on particulate matter (PM) concentration, which results in fundamental or irreparable damages in various socioeconomic aspects. This study investigates the seasonal and spatial distribution characteristics of PM(2.5) concentration in the BTH urban agglomeration and their critical impact factors. Spatial interpolation are used to analyse the real-time monitoring of PM(2.5) data in BTH from December 2013 to May 2017, and partial least squares regression is applied to investigate the latest data of potential polluting variables in 2015. Several important findings are obtained: (1) Notable differences exist amongst PM(2.5) concentrations in different seasons; January (133.10 mg/m(3)) and December (120.19 mg/m(3)) are the most polluted months, whereas July (38.76 mg/m(3)) and August (41.31 mg/m(3)) are the least polluted months. PM(2.5) concentration shows a periodic U-shaped variation pattern with high pollution levels in autumn and winter and low levels in spring and summer. (2) In terms of spatial distribution characteristics, the most highly polluted areas are located south and east of the BTH urban agglomeration, and PM(2.5) concentration is significantly low in the north. (3) Empirical results demonstrate that the deterioration of PM(2.5) concentration in 2015 is closely related to a set of critical impact factors, including population density, urbanisation rate, road freight volume, secondary industry gross domestic product, overall energy consumption and industrial pollutants, such as steel production and volume of sulphur dioxide emission, which are ranked in terms of their contributing powers. The findings provide a basis for the causes and conditions of PM(2.5) pollution in the BTH regions. Viable policy recommendations are provided for effective air pollution treatment.